Physical functioning for prostate health - Segal, Roanne (Canadian Urological Association Journal, 2014)
Men who undergo long-term androgen-deprivation therapy (ADT) may experience systemic side effects similar to the classical metabolic syndrome. Exercise is a potential strategy for offsetting the adverse effects of ADT among patients with prostate cancer, resulting in improved muscular resistance and positive outcomes on body size and composition. Fitness (aerobic capacity), fatigue, and certain quality of life (QOL) outcomes may also improve in response to a regular exercise regimen. Caution and cardiovascular screening is merited given the elderly population with this disease.